Bed-side management of post-operative bleeding in transurethral resection of the prostate--hemostatic trial with thrombin solution injected into the resected cavity of the prostate - Hasegawa, S (Hinyokika kiyo. Acta urologica Japonica, 1987)
To control post-operative bleeding from the resected cavity in transurethral resection of the prostate (TUR-P), 20,000 units of thrombin dissolved in 5-20 ml of physiological saline was injected into the cavity in one shot with a new type of 3-way Foley catheter. The catheter has two holes close to the balloon, and the holes provide outlets through which the solution is directly injected into the cavity. Out of 23 patients between 58 and 87 years old, 11 were given thrombin and 12 were control cases. In each case, urine blood volume (ml/hr) was determined before (a) and after (b) injection. The hemostatic effect was assessed with a "hemostatic index" of b/a. There was a statistically significant difference in the hemostatic indices between thrombin group and the control. (p less than 0.02) This new hemostatic method proved to be a very useful easy bed-side technique to control bleeding even in sudden bleeding after TUR-P. No serious side effects were found during the course of this study